Effect of Mn doping in CdS quantum dot sensitized solar cells grown by SILAR method - Srisomroop, Juthapak; Wichaiyo, Napasuda; Gaewdang, Thitinai; Wongcharoen, Ngamnit; Limsuwan, Pichet; Yindeesuk, Witoon (My University, 2021)
The manganese-doped cadmium sulfide (Mn-doped CdS) quantum dots on titanium dioxide nanoparticles was fabricated using the successive ionic layer absorption and reaction (SILAR) method. The quantum dots were applied to photovoltaic cells. The mixing percentage of manganese in cadmium sulfide precursors was in the range of 1-20 mol%. The study of transport mechanisms and photovoltaic properties of the Mn-doping into CdS QD were investigated using a solar simulator (AM 1.5 G) and current-voltage (J-V) measurements in the dark and under illumination conditions (100 mW/cm2) at room temperature. The photovoltaic performance results indicate that Mn-doped in CdS ratio of 15 mol% exhibits the photovoltaic performance maximum convention efficiency (PCE) is 0.33%. The X-ray diffraction (XRD) patterns of Mn/CdS photoanodes show the nanoparticle average grain size in the range of 4-5 nm, which the formation of the nanoparticles was confirmed by scanning electron microscopy (SEM). The energy dispersion spectroscopy (EDS) shows that Mn is doped into the lattice of CdS QDs. The optical property of the quantum dots was investigated by UV-VIS absorption spectroscopy. The optical band gap was obtained and found to be 2.19 eV from Tauc's plot technique.
Keywords: Cadmium sulfide; Mixing percentage of precursors; Photovoltaic cells; Quantum dot; Successive ionic layer adsorption and reaction